2010
DOI: 10.1002/cncy.20108
|View full text |Cite
|
Sign up to set email alerts
|

The utility of napsin‐A in the identification of primary and metastatic lung adenocarcinoma among cytologically poorly differentiated carcinomas

Abstract: BACKGROUND: New developments in the treatment of lung cancer have necessitated the further histologic and cytologic subtyping of nonsmall cell lung carcinomas. Thyroid transcription factor‐1 (TTF‐1) long has served as the predominant marker for demonstrating lung origin. However, it is also expressed in a variety of other tumors, particularly neuroendocrine neoplasms and, to a much lesser degree, squamous cell carcinoma of the lung. Napsin‐A, which is expressed in lung tissue, is a relatively new marker for lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 24 publications
8
101
2
Order By: Relevance
“…Naps-A was expressed in 4 TTF1À cases (that had CK7 expression only), supporting its role as an additional ADC marker. 25 In TTF1À tumors, coexpression of DSC-3 and p63 supported a diagnosis of SQCC (confirmed in 72.7% of cases at surgery), and proved highly specific for SQCC (SP ¼ 1), irrespective of p63/p40 reactivity. DSC-3 was never seen in association with TTF1, with the exception of the adenosquamous carcinoma having a composite differentiation.…”
Section: Discussionmentioning
confidence: 80%
“…Naps-A was expressed in 4 TTF1À cases (that had CK7 expression only), supporting its role as an additional ADC marker. 25 In TTF1À tumors, coexpression of DSC-3 and p63 supported a diagnosis of SQCC (confirmed in 72.7% of cases at surgery), and proved highly specific for SQCC (SP ¼ 1), irrespective of p63/p40 reactivity. DSC-3 was never seen in association with TTF1, with the exception of the adenosquamous carcinoma having a composite differentiation.…”
Section: Discussionmentioning
confidence: 80%
“…Studies using a monoclonal napsin A antibody to distinguish primary pulmonary from nonpulmonary tumors have reported high specificity. 5,11,12,14 We used a polyclonal napsin A antibody and observed decreased specificity, with napsin A expressed in 48% of extrapulmonary mucinous tumors. One other study has used the same polyclonal antibody used in our study, although with different results.…”
Section: 711-13mentioning
confidence: 99%
“…Studies have shown that thyroid transcription factor 1 (TTF-1) and napsin A are specific markers for primary lung adenocarcinoma (31,32), and that cytokeratin 20 (CK20) and caudal type homeobox 2 (CDX2) positivity supported the diagnose of primary pancreatic cancer (30); however, the positivity rate of TTF-1 and Napsin A is low. Krasinskas et al (30) reported that KRAS G12C mutations, TTF-1 and napsin A are associated with primary lung adenocarcinoma, whereas KRAS G12R mutations, CK20 and CDX2 are more common in pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%